Proposal for peruvian standard considering the effect of bidirectionality and the angle of incidence of an earthquake - Moscoso, Edisson (2019)
Currently, it is considered that seismic actions act independently in two or three main directions orthogonal to each other, applying them to the building, without this necessarily being valid. It is for such, that seismic analysis of buildings should consider the bidirectional effects that seismic actions have, being possible if an angle of real incidence of each seismic action was considered, to estimate the maximum effects of the structural elements. These effects will be analyzed by using the linear time-history analysis of 11 structures with different rigidities and eccentricities in both directions, using angles of incidence every 10° and 20 Peruvian seismic records between very rigid, intermediate and soft soils obtained from data base of CISMID and IGP. Afterwards, a non-linear time-history analysis will be carried out, which will be applied to one of the 11 structures and use angles of incidence every 10° and a seismic record. Likewise, 2 models will be made to scale so that they are tested on a platform of six degrees of freedom, entering the records of the accelerations in their three directions. The maximum responses of all the verifications will be compared with the maximum response of the spectral modal analysis obtaining linear rules for amplification factors. Finally, it will be obtained a relation between the spectral modal analysis and the time-history analysis that consider the effects of the bidirectionality and the angle of incidence in reinforced concrete structures.